THE PARTITION DIMENSION OF ROSE GRAPHS AND ITS BARBELL - Dina Eka Nurvazly; Martha Magdalena Sihombing; Asmiati; Notiragayu (Jurnal Matematika UNAND, 2026)
The rose graph, denoted by R(C_n), n>=3 constructed by a cycle graph C_n with n isolated vertices that connect every two vertices in the cycle graph with one isolated vertex. The rose barbell graph, denoted by B_{R(C_n)} is a simple graph formed by connecting two rose graphs R(C_n) by edges v_1,v^{'}_1 as a bridge. In this paper, we determined the partition dimension of the rose graph and its barbell